Digitalisasi UMKM: Membantu Usaha Kecil Menggunakan Teknologi (Studi Kasus: Desa Melati 2) - Panjaitan, Muhammad Iqbal; Rajagukguk, Denni M; Manalu, Mamed Rofendi; Sihombing, Monang Juanda Tua (Marsipature Hutanabe: Jurnal Pengabdian Kepada Masyarakat, 2024)
The community service program entitled "Digitalization of MSMEs: Helping Small Businesses Use Technology" aims to increase the capacity of Micro, Small and Medium Enterprises (MSMEs) in utilizing digital technology to optimize operations and expand their market reach. MSMEs play an important role in the Indonesian economy, but often face challenges in adopting digital technology due to limited knowledge and resources. The program involves intensive training and hands-on mentoring on the use of digital technology, including online marketing tools, inventory management systems, and e-commerce platforms. The methods used include practical training sessions, workshops and individual mentoring. Evaluations show that participants experienced significant improvements in their technology understanding, digital skills and business performance. The program recommends the need for continued support and better access to technological resources to ensure the success and sustainability of MSME digitalization in the future.